ANALISIS INSTRUMEN DAN KLASIFIKASI MAQASHID SHARIA UNTUK KEBERLANJUTAN EKONOMI: STUDI KASUS BANK SYARIAH INDONESIA - Sari Dewi; Antony Antony; Nany Tan; Kelvin Andreas; Julia Julia; Charline Marshella Ong; Sisilia Wijayanti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to analyze the financing instruments of Bank Syariah Indonesia, a financial institution in the banking sector that operates on Sharia principles in accordance with Islamic teachings. The analyzed instruments include mudharabah, musyarakah, ijarah, istishna, and murabahah financing. This study applies a qualitative approach with a literature review method and document analysis, facilitating data collection from secondary sources and allowing for the analysis of the percentage of financial instruments in relation to total financing. The research results reveal the trend of fund allocation by Bank Syariah Indonesia across the five types of instruments, along with their contributions as a percentage of total financing. In this context, murabahah and musyarakah instruments dominate with significant contributions, while mudharabah, ijarah, and istishna instruments have lower contributions. Additionally, this research classifies financing instruments based on the social pyramid of maqashid sharia, resulting in an in-depth analysis of the suitability of financing aspects in adhering to Sharia principles